ANALISIS RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS DALAM MENGUKUR KINERJA KEUANGAN - Rona, Riza; Gafar, Muammar Saidul; Novita, Mutia (JURNAL LENTERA BISNIS, 2026)
This study aims to determine the level financial performance of PT. Wijaya Karya (Persero) Tbk. which is reviewed based on the Analysis of Liquidity Ratio, Solvency Ratio and Profitability Ratio. From 2020 to 2022. The research method used is quantitative descriptive method and secondary data sources. The results of the study based on the calculation of the liquidity ratio show that the company in 2020 to 2022 the company is not liquid, because the average internal company current ratio is 103% ≤ 200%, cash ratio 22% ≤ 50% and quick ratio 77% ≤ 100%. The financial performance of PT. Wijaya Karya (Persero) Tbk reviewed from solvency shows that the company is not solvable. Because the average internal company debt to total assets ratio is 75% ≥ 35% and debt to equity ratio is 311.33% ≥ 90%. and the financial performance of PT. Wijaya Karya (Persero) Tbk. In terms of profitability, it also shows that the company is non-profit. Measured using the company's average internal net profit margin of 0.88% ≤ 20%, and based on return on equity (ROE) it shows 0.76% ≤ 40% and based on return on assets (ROA) it shows 0.163% ≤ 30%. This indicates that financial performance is still below the industry average ratio standard.